Respostas
respondido por:
6
Olá!!!
Resolução!!
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
6x + 2x = 8
8x = 8
x = 8/8
x = 1
S = { 1 }
Espero ter ajudado!!!
Resolução!!
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
6x + 2x = 8
8x = 8
x = 8/8
x = 1
S = { 1 }
Espero ter ajudado!!!
Anônimo:
Ajudou
respondido por:
3
Olá
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
8x = 8
x = 8/8
x = 1
Bons estudos
7x - 3 = x + 5 - 2x
7x - x + 2x = 5 + 3
8x = 8
x = 8/8
x = 1
Bons estudos
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás